Kajian Hypothetical Learning Trajectories dalam Pembelajaran Matematika di Tingkat SMP - Agnes Ivana Hendrik; Christine K Ekowati; Damianus D Samo (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2020)
Mathematics learning in this era requires teachers to be able to develop learning models that pay attention to the characteristics of students, so it is important for teachers to know learning trajectory. This study aims to describe the conception of learning trajectory and hypothetical learning trajectory, as well as presenting the design of hypothetical learning trajectories in mathematics learning. Based on the theories studied, it is concluded that hypothetical learning trajectory is a learning design in the form of allegations on student learning activities based on initial understanding and characteristics of students to achieve higher understanding. HLT has three main components namely learning objectives, learning activities, and hypotheses of the learning process. HLT is used by teachers as a guide to predict and prepare learning flow designs that are appropriate to the stages of student thinking and can improve student learning outcomes. The findings of previous studies show that to design HLT in mathematics learning, educators need to consider student obstacle learning, a hierarchy of material, and learning support capacity, so that learning activities to be hypothesized are built based on these things. It is recommended that future researchers can use the existing HLT, and also develop HLT in other materials that have not been tested by further studying HLT and whatever affects it, research with different differences can be used.